Why so Many Programming Languages - Mehra, Sparsh (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
Programming is a basic course that is instructed to each computer science during their underlying semesters. The course acquaints the understudies with nuts and bolts tasks and engineering of computers, and furthermore cleans the critical thinking abilities of understudies. Other than these benefits, programming language fills in as a basic device for examining, studying and understanding progressed ideas of computer science that the understudies are instructed in later semesters of their undergrad contemplates. Subsequently, the determination of a programming language for teaching to computer science understudies is critical. During the beyond couple of years, there have been various programming languages developed, for example, COBOL, FORTRAN, Algol, Miranda, Oberon, Ada and Java and so forth With the progression of time, some these languages have lost unmistakable quality while a few new languages have arisen. Hence, the determination of a programming language for teaching has consistently stayed a significant examination question for academicians. In this paper, a comparative investigation of contemporary programming languages is performed. After a cautious assessment of current educational plan and market requests, we have chosen C/C++, C#, Java, Pascal, GW Basic and JavaScript for examination. The target of this study is to figure out which programming language languages ought to be educated to computer science understudies at introductory level. The paper investigates the chose programming languages dependent on various boundaries and gives suggestions on the choice of programming language.